The moderating role of board gender diversity: leverage and tax avoidance - Jimmy, Jimmy; Firmansyah, Amrie; Trisnawati, Estralita (WIM Solusi Prima, 2025)
This study examines the effect of leverage on tax avoidance, and also examines the moderating influence of the director's gender diversity in that relationship, particularly in the property and real estate sector. This study uses secondary data, which is the annual reports of companies listed in the Indonesian Stock Exchange for the period 2021-2023, retrieved from www.idx.co.id. Based on purposive sampling, the total samples are 87 observations. The analytical method of this study is multiple linear regression analysis with a random effect approach for panel data. The result shows that leverage has a negative effect on tax avoidance, and director gender diversity doesn’t succeed in moderating the positive influence of leverage on tax avoidance in property and real estate companies that are listed on the Indonesian Stock Exchange for the years 2021-2023. This study provides implications for the Directorate General of Taxes (DGT) in mapping the characteristics of companies that are prone to tax avoidance.